STRATEGI PENANAMAN NILAI MODERASI BERAGAMA: STUDI DI SEKOLAH MENENGAH ATAS NEGERI 1 MATARAM - A.Zuhruddin Hadi Saputra; Muh. Wasith Achadi (El-Tsaqafah : Jurnal Jurusan PBA, 2025)
This research is based on the importance of the role of teachers of Islamic Religious Education in shaping a moderate attitude amidst the diversity of students, so that a tolerant, harmonious learning environment is created in accordance with the values of rahmatan lil ’alamin. The study aims to identify the steps of teachers’ strategies in Islamic Religious Education in instilling the values of religious moderation among students at SMA Negeri 1 Mataram. The research uses a qualitative approach with a case-study design. The subjects of the study are teachers of Islamic Religious Education and students of SMA Negeri 1 Mataram. Data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman model. Theoretically, this research is expected to enrich the body of scientific knowledge and serve as a reference for future researchers in developing inclusive and moderate education.